Nutrient restriction does not affect implant efficacy - Lee, T.; Mamedova, Laman K.; Wileman, Benjamin W.; Thomson, Daniel U.; Bradford, Barry J.; Reinhardt, Christopher D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Anabolic implants in finishing beef cattle offer significant return on investment. Anabolic implants improve average daily gain feed efficiency in pasture and feedlot cattle. One way growth-promoting implants stimulate growth is through increasing production of insulin-like growth factor 1. This hormone causes muscle cells to increase their uptake of glucose and amino acids from the bloodstream. Plasma urea nitrogen is a simple measure of the protein nutritional status of animals. If lean growth is stimulated, more feed protein is utilized and retained as body protein, reducing the amount of circulating plasma urea nitrogen. If an animal is stressed and is not growing, more of the feed protein is broken down, processed, and excreted as urea nitrogen.
Beef Cattle Research, 2011 is known as Cattlemen’s Day, 2011
Keywords: Beef; Anabolic implant; Average daily gain; Protein; Nitrogen